Subarctic physicochemical weathering of serpentinized peridotite - Ulven, O.; Beinlich, Andreas; Hövelmann, J.; Austrheim, H.; Jamtveit, B. (Elsevier BV, 2017)
Frost weathering is effective in arctic and subarctic climate zones where chemical reactions are limited by the reduced availability of liquid water and the prevailing low temperature. However, small scale mineral dissolution reactions are nevertheless important for the generation of porosity by allowing infiltration of surface water with subsequent fracturing due to growth of ice and carbonate minerals. Here we combine textural and mineralogical observations in natural samples of partly serpentinized ultramafic rocks with a discrete element model describing the fracture mechanics of a solid when subject to pressure from the growth of ice and carbonate minerals in surface-near fractures. The mechanical model is coupled with a reaction–diffusion model that describes an initial stage of brucite dissolution as observed during weathering of serpentinized harzburgites and dunites from the Feragen Ultramafic Body (FUB), SE-Norway. Olivine and serpentine are effectively inert at relevant conditions and time scales, whereas brucite dissolution produces well-defined cm to dm thick weathering rinds with elevated porosity that allows influx of water. Brucite dissolution also increases the water saturation state with respect to hydrous Mg carbonate minerals, which are commonly found as infill in fractures in the fresh rock. This suggests that fracture propagation is at least partly driven by carbonate precipitation. Dissolution of secondary carbonate minerals during favorable climatic conditions provides open space available for ice crystallization that drives fracturing during winter. Our model reproduces the observed cm-scale meandering fractures that propagate into the fresh part of the rock, as well as dm-scale fractures that initiate the breakup of larger domains. Rock disintegration increases the reactive surface area and hence the rate of chemical weathering, enhances transport of dissolved and particulate matter in the weathering fluid, and facilitates CO2 uptake by carbonate precipitation. Our observations have implications for element cycling and CO2 sequestration in natural gravel and mine tailings.